The Analysis of Fifth-Grade Students' Creativity in the Subject of Maintaining Human Health through Assignments - Rasmiati, Iras; Sujana, Atep; Sopandi, Wahyu (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2024)
Creativity is something that is very important to be a provision for students in living their lives in the future, especially in modern times like today. The purpose of this study was to analyze the creativity of students in elementary school through assignments. The method used is qualitative descriptive. The instruments used in this study were interview sheets and observation sheets regarding indicators of creativity carried out by students. The subjects in this study were grade 5 students with a total of 29 people consisting of 16 men and 13 women in one of the State Elementary Schools located in Cibatu District. The results showed that through the specific assignment of project assignments in the learning process, on the material of maintaining human health, students can show new creativity and benefit themselves. The emergence of creativity can be illustrated from the results of programs that have very interesting imagination results, the authenticity of the results of the products from the students themselves, the results of products that have very useful values and goals. Student-produced products such as drawings, poems, songs, and comics, can be viewed as simple but meaningful results of student creativity, and have useful purposes. Students are also more challenged to create something even better and truly their own work without imitating the work of others. In conclusion, the results of the analysis of student creativity through assignments can bring out the creativity of students who initially did not want to try to be more courageous trying to make simple works, Although only some students can bring it up, it can be said that project assignments can make students have a sense of responsibility and time discipline in completing their obligations in the learning process.